Комплексний алгоритм функціонування систем радіоакустичного зондування атмосфери - Карташов, О. В. (ХНУРЕ, 2023)
The article presents a synthesis of the structural diagram of a promising radioacoustic measuring complex and a complex algorithm of its functioning. It is shown that the development process of RAVC can be reduced to the development of the following independent issues: synthesis (selection) of types of sounding radio and acoustic signals, their energy parameters, synthesis of spatial and temporal signal processing algorithms for optimal selection of useful information from signals received against a background of noise, development of complex management algorithms and complex adaptation to external conditions formed by the external environment, as well as development of technical means intended for the implementation of the specified algorithms.
Keywords: зондування атмосфери